Biofortification: harnessing agricultural technology to improve the health of the poor - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
This brief discusses a new breed of ultra-nourishing crops capable of alleviating malnutrition in even the most hard-to-reach populations—crops such as rice loaded with iron, maize packed with zinc, and wheat strengthened with vitamin A. These staples would need no commercial fortification, and could be grown on family plots throughout the developing world. It is now possible to breed plants for increased vitamin and mineral content, making “biofortified™” crops one of the most promising new tools in the fight to end malnutrition and save lives. The authors conclude that biofortification makes sense as part of an integrated food systems approach to reducing malnutrition. It addresses the root causes of micronutrient malnutrition, targets the poorest people, uses built-in delivery mechanisms, is scientifically feasible and cost-effective, and complements other on-going methods of dealing with micronutrient deficiencies.